2006
DOI: 10.1128/jcm.02039-05
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Variable-Number Tandem-Repeat Markers for Typing of Brucella spp

Abstract: Members of the genus Brucella infect many domesticated and wild animals and cause serious zoonotic infection in humans. The availability of discriminatory molecular typing tools to inform and assist conventional epidemiological approaches would be invaluable in controlling these infections, but efforts have been hampered by the genetic homogeneity of the genus. We report here on a molecular subtyping system based on 21 variable-number tandem-repeat (VNTR) loci consisting of 13 previously unreported loci and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
159
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 28 publications
12
159
1
1
Order By: Relevance
“…Some investigators reported that MLVA could classify Brucella isolates in accordance with different host origin (Groussaud et al, 2007), geographic region (Kattar et al, 2008), and species (Whatmore et al, 2006). In clustering and traceback analysis, B. abortus isolates from wild animals were included in the same group as isolates from livestock, suggesting that direct or indirect horizontal transfer may occur and that brucellosis in wildlife reservoirs may pose a threat to humans and domestic animals.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Some investigators reported that MLVA could classify Brucella isolates in accordance with different host origin (Groussaud et al, 2007), geographic region (Kattar et al, 2008), and species (Whatmore et al, 2006). In clustering and traceback analysis, B. abortus isolates from wild animals were included in the same group as isolates from livestock, suggesting that direct or indirect horizontal transfer may occur and that brucellosis in wildlife reservoirs may pose a threat to humans and domestic animals.…”
mentioning
confidence: 96%
“…The MLVA typing assay has been recommended by many researchers to analyze the genetic diversity and to trace the origins of infection (Whatmore et al, 2006;Al Dahouk et al, 2007;Groussaud et al, 2007;Her et al, 2009;Kang et al, 2009;Abril et al, 2011). Seventeen markers (16 loci and HOOF-3) used previously were available for follow-up (Bricker et al, 2003;Her et al, 2009).…”
mentioning
confidence: 99%
See 3 more Smart Citations